Iron–Oxalato Framework with One‐Dimensional Open Channels for Electrochemical Sodium‐Ion Intercalation. Issue 3 (17th November 2014) - Wang, Xianfen; Kurono, Ryosuke; Nishimura, Shin‐ichi; Okubo, Masashi; Yamada, Atsuo
Abstract Discovery of a new class of ion intercalation compounds is highly desirable due to its relevance to various electrochemical devices, such as batteries. Herein, we present a new iron–oxalato open framework, which showed reversible Na+ intercalation/extraction. The hydrothermally synthesized K4Na2[Fe(C2O4)2]3⋅2 H2O possesses one‐dimensional open channels in the oxalato‐bridged network, providing ion accessibility up to two Na+ per the formula unit. The detailed studies on the structural and electronic states revealed that the framework exhibited a solid solution state almost entirely during Na+ intercalation/extraction associated with the reversible redox of Fe. The present work demonstrates possibilities of the oxalato frameworks as tunable and robust ion intercalation electrode materials for various device applications.